Whānau experiences of supporting a hospitalised family member away from their home base - Bridgette Masters-Awatere; Donna Cormack; Rebekah Graham; Amohia Boulton; Rachel Brown; Makarita Tangitu-Joseph (Kōtuitui, 2024)
ABSTRACTIn Aotearoa New Zealand, accessing the required level of hospital care can mean a patient is transferred away from their home base. Being transferred away from familiar surroundings inequitably impacts on people who live in rural areas, including Māori. During such transfers, whānau (family) of Māori patients who travel to support their unwell family member are also away from wider support systems. This paper presents the findings of 17 semi-structured interviews with 19 whānau from across the Central North Island region. Whānau discuss their experiences of being away from home and of providing support to their hospitalised whānau member. Our analysis draws out nuanced responses regarding communication of information and access to the wider service-scape. Experiences and challenges are discussed within a context of inequity, produced vulnerability, and the impact of distress and emotionality. Implications are considered in light of the global pandemic and recent health system reform, offering suggested ways to navigate Māori whānau remaining engaged in the care of their loved one during a hospital transfer.